Measuring the quality of educational services from the perspective of students (Comprehensive Journal of Science, 2024)
The quality of educational services provided to students goals clear to those in charge of the Higher Institute of Technical Sciences, to cover the modern aspects of the relationship between the Institute and its students, and therefore this study seeks to measure the quality of educational services provided by the institute under study for his students that, using a scale (Service Quality Model), which known simply as (SERVQUAL), and determine whether there was a gap between students' expectations and their perception of the quality of these services, the researcher suggested set of results was the most important: the existence of a statistically significant difference between the perception of students and their expectations for the level of quality of educational services provided by the departments concerned students including scientific departments, registration and examinations, as well as having a negative gap between students' awareness of the level of the quality of educational services actually provided to the students on the one hand and their expectations for the level of quality of such services on the other hand, after measuring the quality of services provided by the institute under study researcher found that the quality level is the average from the viewpoint students, as well as the lack of statistically significant differences in students' assessment of the level of the quality of educational services actually provided by the institute attributed the following demographic variables (gender, scientific section, grade), and through those results is recommended to improve the quality of services provided to students level researcher, particularly with the development and improvement of the concrete aspects and reliability aspects and aspects of empathy. Which represent great importance in improving the overall level of quality educational services and development, as well as increased attention to safety next to me and respond in educational institute services.